Interventions to Reduce Mental Health Stigma and Discrimination A Literature Review to Guide Evaluation of California's Mental Health Prevention and Early Intervention Initiative - Collins, Rebecca L. (RAND Corporation, 2012)
A number of programs aim to reduce the stigma and discrimination associated with mental illness, and they can include a variety of components such as training, education, media campaigns, and contact with people with mental illness. Stigma and discrimination reduction activities are evaluated in this report, using evidence from an extensive literature review.